The Influence of Independence, Locus of Control, Professional Skepticism and Auditor Experience on Audit Judgment (Study on Public Accounting Firms in Semarang) - Saputri, Nazlia Hilda; Khatik, Nur (Economics and Business International Conference Proceeding, 2024)
Financial report users need financial statements that are able to provide reliable, comprehensive and easy-to-understand information so that they can be used as a basis for decision-making. The purpose of this research is to test and find empirical evidence of the influence of independence on audit judgment. To test and find empirical evidence of the influence of locus of control on audit judgment. to test and find empirical evidence of the influence of professional skepticism on audit judgment. to test and find empirical evidence of the influence of auditor experience on audit judgment. The method in this study is quantitative. The result of this study is that the higher the independence of the auditor, the better the audit judgment will be given. The higher the locus of control owned by the auditor, the self-control owned by the auditor will also increase so that the audit judgment given will be better. The higher the professional skepticism of the auditor, the better the audit judgment will be given. The higher the experience that the auditor has, the better the consideration in the audit.